Dynamic economic decision making strategies for financial risk, capital markets, and monetary policy - Silvia, John (Wiley finance series., 2011)
"A comprehensive analysis of the macroeconomic and financial forces altering the economic landscapeFinancial decision-making requires one to anticipate how their decision will not only affect their business, but also the economic environment. Unfortunately, all too often, both private and public sector decision-makers view their decisions as one-off responses and fail to see their decisions within the context of an evolving decision-making framework.In Decision-Making in a Dynamic Economic Setting, John Silvia, Chief Economist of Wells Fargo and one of the top 5 economic forecasters according to Bloomberg News and USA Today, skillfully puts this discipline in perspective. Details realistic, decision-making approaches and applications under a broad set of economic scenarios Analyzes monetary policy and addresses the impact of financial regulations Examines business cycles and how to identify economic trends, how to deal with uncertainty and manage risk, the building blocks of growth, and strategies for innovation Decision-Making in a Dynamic Economic Setting details the real-world application of economic principles and financial strategy in making better business decisions"--